Communicating deprescribing decisions made in hospital with general practitioners in the community. Issue 9 (19th September 2021) - Nguyen, Amy D.; Baysari, Melissa T.; Duong, Mai; Zheng, Wu Yi; Ng, Brendan; Lo, Sarita; Robinson, Fiona; Hilmer, Sarah N.
Abstract: Background: Deprescribing, the supervised withdrawal of inappropriate medications, intends to manage polypharmacy, which is prevalent in older patients. Aims: To examine general practitioner (GP) perceptions of communication processes between clinicians in hospital and GP in the community about deprescribing decisions made in hospital. Methods: Focus groups and interviews were held with 15 GP, exploring deprescribing in hospitals, communication of deprescribing information and the format of communications. Sessions were audiotaped, transcribed and analysed using an inductive approach. Results: GP stated that they should be involved in deprescribing decisions, especially for older complex patients, because of their good knowledge of their patients. Barriers to effective communication included the acute nature of hospital stays and lack of time. Facilitators included long‐term relationships of GP with their patients and engaged patients. GP preferred communication of deprescribing decisions to be over the telephone while the patient was still in hospital, and with a concise, electronic discharge summary at the time of discharge. GP indicated that rationale for medication changes and recommended follow‐up actions were crucial in a discharge summary to enable care post‐discharge. Conclusions: GP welcome increased communication with hospital clinicians regarding deprescribing decisions made while patients are in hospital. Communication needs to be timely, transparent, succinct and accessible. Lack of time and difficulties contacting hospital clinicians challenge this process.